Nursing Faculty Competencies to Produce Nursing Graduates in response to Population Health Needs in Thailand - Charoensuk, Dr.Sukjai; Sitanon, Thongsouy; Turner, Kamolrat; von Bormann, Suparpit; Sawaengdee, Krisada (Journal of The Royal Thai Army Nurses, 2019)
Nursing faculty is recognized as a key person in producing nurses to address population health needs. The current population needs demand competent nurses to response effectively. Nursing faculty plays an important role in teaching pre-licensing nursing students to be qualified nurses. However, a little is known about competencies of nursing faculty members in Thailand. This study aimed to identify and propose a "model faculty member" in nursing in response to health needs of the population. Descriptive qualitative methods were applied. Review literature on faculty competencies in education and nursing profession lead researchers to develop semi-structure interview guide for focus group of stakeholders. Qualitative data from 3 groups of stakeholders, including 8 nursing students, 6 health sector employers, and 9 faculty members and administrators, were analyzed using content analysis combined with data from literature to formulate the model of faculty competencies. The propose model was validated by a group of 9 experts in nursing education. The result revealed that the model faculty composed of five key competencies, namely 1) nursing competencies, 2) pedagogy competencies, 3) personal development competencies, 4) ethical and moral competencies, and 5) research and academic services competencies. The finding is benefit to prepare the faculty necessary to educate future generations of nurses.